A Dangerous Consequence of the Recent Pandemic: Early Lung Fibrosis Following COVID-19 Pneumonia – Case Reports - Scelfo C; Fontana M; Casalini E; Menzella F; Piro R; Zerbini A; Spaggiari L; Ghidorsi L; Ghidoni G; Facciolongo NC (Dove Medical Press, 2020)
Chiara Scelfo,1 Matteo Fontana,1 Eleonora Casalini,1 Francesco Menzella,1 Roberto Piro,1 Alessandro Zerbini,2 Lucia Spaggiari,3 Luca Ghidorsi,1 Giulia Ghidoni,1 Nicola C Facciolongo1 1Department of Medical Specialties, Pneumology Unit, Azienda Unità Sanitaria Locale-IRCCS di Reggio Emilia, Reggio Emilia, Italy; 2Unit of Clinical Immunology, Allergy and Advanced Biotechnologies, Azienda Unità Sanitaria Locale-IRCCS di Reggio Emilia, Reggio Emilia, Italy; 3Department of Radiology, Azienda Unità Sanitaria Locale-IRCCS di Reggio Emilia, Reggio Emilia, ItalyCorrespondence: Chiara Scelfo Email chiara.scelfo@ausl.re.itAbstract: The outbreak of the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) started in China in December 2019. COVID-19 patients at presentation show a wide spectrum of clinical and pathological involvement. We report two cases of respiratory insufficiency due to COVID-19 pneumonia that occurred in adults without a history of respiratory diseases. Although these patients improved and were discharged from the acute ward, during the hospitalization they both progressed with a subsequent clinical and radiological worsening, pointing out one of the main concerns for these patients at discharge: the possibility of developing persistent lung abnormalities also in healthy people not having other risk factors. In conclusion, these cases represent two examples of early lung fibrosis in patients with COVID-19 pneumonia with different severity disease evolution and highlight the need for long-term follow-up strategies. The etiology of this fibrosis is under discussion: we suppose that it could be due to either a possible outcome of natural history of lung damage produced by ARDS, or to the lung injury related to high oxygen level or to the lung damage directly induced by viral infection or finally to the autoimmune response. At this moment, it is not possible to predict how many people will have consequences due to COVID-19 pneumonia, and therefore we believe that careful follow-up should be mandatory.Keywords: COVID-19, pulmonary fibrosis, critical care, viral disease, computed tomography, follow-up